The teaching of history in post-genocide Rwanda: a case-study of a post-genocide secondary school history curriculum - Kehoe, Earl (2016)
The focus of this thesis is an investigation of secondary school history in post-genocide Rwanda. The thesis addresses a knowledge gap by examining the 2008 O-level Rwandan history curriculum as a case of a post-genocide secondary school history curriculum. The issues surrounding the construction of the 2008 O-level history curriculum and the wider opportunities and challenges of teaching and learning history in Rwandan schools are addressed. The research is located in the field of literature that investigates school history in different post-genocide and post-conflict countries and the connections between history education, conflict, peace and reconciliation. Research involved two periods of fieldwork in Rwanda of 11 weeks and 16 weeks respectively. During this time curriculum documents were collected and field-notes taken. Also, interviews were conducted with Rwandan policy-makers (3), secondary history teacher-educators (5) and secondary history student-teachers (10). Informal discussions were held with four additional policy-makers. The empirical research was related to the research question: What opportunities and challenges does teaching history face in post-genocide Rwanda - perceptions of what, why and how history is taught to secondary school pupils? A thematic analysis of the data resulted in three key inter-related findings. Firstly, there are competing policy visions and curriculum processes at the heart of the 2008 O-level secondary school history curriculum. Secondly, the memory of the 1994 genocide is central to the 2008 O-level history curriculum construction (policy), mediation (teacher-educators) and implementation (student-teachers). Finally, and related to finding two above, limited learner-centeredness in student-teachers’ classroom practice demonstrates how the legacy of the Rwandan 1994 genocide impacts on the delivery of the 2008 O-level history curriculum. Based on these findings the thesis makes three original contributions to knowledge. The legacy of the genocide in terms of post-genocide fears of future violence and aspirations for unity and reconciliation needs to be at the centre of our understanding of school history curriculum reform in post-genocide Rwanda. Also, over 20 years after the 1994 genocide the on-going emotional legacy of the genocide in the classroom shapes the classroom practice of a new and university trained generation of history teachers. Yet, student-teacher classroom practice also challenges the uniform depiction of teacher-led history teaching by writers, suggesting a more complex history classroom reality. Finally, this is the first empirical study to use the theoretical framework of ‘unity in homogeneity’, ‘unity in diversity’ and ‘diversity’ approaches to frame and investigate the opportunities and challenges the teaching of history faces in post-genocide Rwanda.